2020
DOI: 10.3389/fphar.2020.582680
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and Cardiovascular Disease: An Update From Molecular Mechanism to Clinical Perspective

Abstract: Uric acid (UA) is the end product of purine nucleotide metabolism in the human body. Hyperuricemia is an abnormally high level of UA in the blood and may result in arthritis and gout. The prevalence of hyperuricemia has been increasing globally. Epidemiological studies have shown that UA levels are positively correlated with cardiovascular diseases, including hypertension, atherosclerosis, atrial fibrillation (AF), and heart failure (HF). Hyperuricemia promotes the occurrence and development of cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
159
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(168 citation statements)
references
References 120 publications
1
159
3
5
Order By: Relevance
“…[ 28 ] XO inhibitor, has been shown to improve cardiovascular outcomes in patients with heart failure and coronary heart disease. [ 29 ] In the present study, higher concentrations of MDA and XO were detected in the serum of patients with heart failure before treatment, and the concentration measured after treatment was significantly lower than the value detected before treatment. A significant increase in the efficacy of the rhBNP treatment was observed after 1 week and the efficacy of the sequential treatment was also significantly increased at 1 week of treatment and persisted to 36 weeks of treatment.…”
Section: Discussioncontrasting
confidence: 48%
“…[ 28 ] XO inhibitor, has been shown to improve cardiovascular outcomes in patients with heart failure and coronary heart disease. [ 29 ] In the present study, higher concentrations of MDA and XO were detected in the serum of patients with heart failure before treatment, and the concentration measured after treatment was significantly lower than the value detected before treatment. A significant increase in the efficacy of the rhBNP treatment was observed after 1 week and the efficacy of the sequential treatment was also significantly increased at 1 week of treatment and persisted to 36 weeks of treatment.…”
Section: Discussioncontrasting
confidence: 48%
“…A recent review on the role of UA in cardiovascular diseases (CVD) has focused on summarizing the association between uric acid and various cardiovascular diseases, mainly from experimental evidence (13). Also, the review was shallow in the area of AF despite its well-organized content on the relationship between UA and CVD.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that hyperuricemia incidence is increasing and it has become the "fourth highest" risk factor after hyperlipidemia, hypertension and hyperglycemia [49], It is reported that there were 32.5 million patients with hyperuricemia in the United States [50] and 170 million in China [51]. There is strong epidemiological evidence that hyperuricemia is an important risk factor in several complications, such as chronic kidney disease, obesity, hypertension, and type 2 diabetes mellitus [52].…”
Section: Discussionmentioning
confidence: 99%